Parental psychological distress and child maladjustment: Exploring the moderating role of sibling relationship quality - Jessica Turgeon; Jean-François Bureau (Frontiers in Psychology, 2022)
The aim of this study was to investigate whether the quality of the sibling relationship moderates the association between parental psychological distress and child maladjustment (i.e., internalizing and externalizing problems). We extended previous literature by studying mothers and fathers separately and by including an observational measure of the quality of the sibling relationship. Participants were 52 two-parent families from a community sample who had at least two children living at home. Only one child (aged 6–10 years) was targeted for the study and studied in relation to his/her siblings. Mothers and fathers completed a self-reported questionnaire on their psychological distress and individually assessed their child’s social-emotional maladjustment. The targeted child’s interactions with his/her siblings were observed by independent judges during a home-visit. Results indicate that both maternal and paternal psychological distress are significant predictors of child social-emotional maladjustment. Moderation analyses reveal that children of distressed fathers are at lower risk of social-emotional maladjustment when they engage in highly positive interactions with their siblings. Post hoc analyses suggest that only sibling empathy (not teaching nor companionship) is a significant moderator of the association between paternal psychological distress and child maladjustment. The results of this study provide further evidence of the influence that fathers have in their child’s development and highlight the importance of using a systemic family approach to promote children’s social-emotional adaptation in the context of parental distress.